Does Green Thinking Lead to Green Purchasing? Determinants of Sustainable Consumption Behavior of Indonesian Muslim Scholars - Susanti, Vitria Susanti; Zuliansyah, Ahmad; Yama, Arifeen (IKONOMIKA, 2025)
The growing awareness of climate change and environmental issues has led to the rise of green consumerism and heightened global environmental concerns. As individuals become more mindful of their role in preserving the environment, green consumerism has gained significant traction. This research is distinctive in its integration of Islamic religiosity and environmental concern as additional factors within the Theory of Planned Behavior (TPB), a widely established framework in behavioral studies. Using a quantitative approach, the study investigates the factors shaping sustainable behavior among Muslim academics in Indonesia, with an emphasis on expanding the TPB by incorporating two new variables: religiosity and environmental concern. The results highlight a discrepancy between attitudes and behaviors, particularly in relation to green purchasing patterns. These findings contribute to the development of the TPB, enhancing its explanatory power by including religious and environmental concerns as key determinants of sustainable consumption behavior.